The read-out ASIC for silicon drift detectors. Issue 4 (January 2016) - Atkin, E; Ivanov, P; Krivchenko, A; Levin, V; Gusev, A; Malankin, E; Normanov, D; Rotin, A; Sagdiev, I; Shumikhin, V
Abstract: The paper describes the read-out ASIC for silicon X-ray drift detectors. The ASIC has been designed in CMOS 0.35 μm technology and contains two read-out channels. Each channel includes a preamplifier and shaper. The preamplifier in the first channel has a built-in input transistor, the preamplifier in second channel works with an external JFET, which is built in the detector structure. Preamplifiers have been optimized for operation with detectors with capacitances of 100 fF. The 6-th order shaper has controllable time constants (0.5 - 8 μs).